IMPLEMENTASI UNDANG-UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK REPRODUKSI PEREMPUAN PERSPEKTIF HUKUM ISLAM - Atika, Atika (Nurani, 2019)
Reproduction rights are part of human rights that are recognized by national law, international documents on human rights, and other treaty or treaty documents. According to the current reality, reproductive rights for working women have not been implemented well and many female workers still feel discriminated against at work, not in accordance with human rights. In Palembang, a large number of factories still employ female workers. Most of these factories are not open and do not want to provide information about the implementation of Law No. 39 of 1999 concerning Human Rights. Therefore, researchers need to investigate, see the reality, and analyze it through Islamic Law on the Protection of the Implementation of the reproductive rights of women workers in Palembang. This research is focused on PT HEVEA MK I Palembang because the ratio of male and female workers is very sharp. The results showed that several companies in Palembang had not adopted constitution No. 39 of 1999 and the labor constitution for women workers. However, PT HEVEA MK I Palembang has adopted constitution number 39 of 1999 and a labor constitution for women workers. According to Islamic law, companies that implement constitution No. 39 of 1999 and the labor constitution for women workers have adopted the values ​​of Islamic law while the rest do not apply it contrary to Islamic law.